Genital tract infections in HIV‐infected pregnant women in South West London. (May 2020) - Hegazi, A; Ramskill, N; Norbrook, M; Morgan, T; Dwyer, E; Elgalib, A; Renshaw, J; Whittaker, W; Milne, S; Barbour, A; Nathan, B; Iqbal, F; et al.
There are minimal UK data on the prevalence of genital tract infections in HIV‐infected pregnant women. British HIV Association guidelines suggest sexually transmitted infection (STI) screening as early as possible in pregnancy with consideration given to repeat at 28 weeks' gestation. A retrospective case notes review of HIV-infected pregnant women at four South London HIV Centres (1 January 2004–1 January 2014) was carried out. Five hundred and ninety-eight pregnancies in 384 patients were identified. Median age 32 years (interquartile range [IQR] 27–36) and 96% (n = 346) were heterosexually infected. HIV was diagnosed antenatally in 21% of pregnancies (n = 107). Seventy-seven per cent of women (n = 384) were of Black African ethnicity and 75% were born in sub-Saharan Africa with 14% UK-born. The majority of pregnancies (279/507) were reported to be unplanned with 42 women proceeding to termination of pregnancy. A regular male partner was reported in 95% of pregnancies (n = 539) with median relationship duration (n = 347) of four years (IQR 1.5–7.0); 11/324 (3.4%) women reported additional sexual partners during the pregnancy. 76.6% (n = 427) of women had an initial STI screen which was done in the first trimester in 52.1%; 32.1% of women had a repeat STI screen in pregnancy, 96% of which was done in the third trimester. Overall, 61 (14.3%) women were diagnosed with at least one STI during their pregnancy. Vaginal candidiasis and bacterial vaginosis were diagnosed in 27.6% (n = 100) and 21.7% (n = 73) of pregnancies, respectively. STI prevalence was low and obstetric outcomes favourable in this cohort of women. Further information about STI prevalence in this population may impact future screening guidelines.